Estudo dos sintomas do tipo delirium causados por levofloxacina em camundongos submetidos ao modelo inflamatório induzido por lipopolissacarídeo - Lima, Klistenes Alves de (2024)
Delirium is a clinical syndrome of acute brain dysfunction characterized by a state of confusion with decline in cognition that fluctuates over hours or days. It is associated with devastating stages, including increased hospital admissions and high rates of morbidity and mortality. It is correlated to several environmental, medicinal or pathological factors. However, the literature on delirium or psychosis associated with fluoroquinolone use is limited to case reports and the precise mechanism behind this association is unknown. Given the above, it is relevant to propose a possible mechanism for this brain dysfunction that may be caused by this class of antibiotics. To this end, healthy male Swiss mice (22 - 28g) were treated with levofloxacin (100mg/kg and 150mg/kg every 24 hours), or scolopolamine (1.5mg/kg), or vehicle intraperitoneally for 10 days. On the 9th day of treatment, some experimental groups received lipopolysaccharide (LPS) 0.5mg/kg intraperitoneally to activate the immune response. The animals were subjected to behavioral tests evaluating locomotor activity (Open Field), depressive-like behavior (Requested Swimming), cognitive performance (Y-Maze) and motor development (Rota-Rod). After the behavioral assessment, the cognitive areas (prefrontal cortex, striatum and hippocampus) were dissected to evaluate oxidative stress parameters (MDA, nitrite and GSH) and neurotransmitter levels (DOPA, DOPAC, GABA and Glutamate). Cytokines (TNF-α and IL-1β) were measured in serum. The hippocampi were found for analysis of the following parameters: cellular targets; histopathological changes; expression of markers of astrocytic reactivity and glial activation (GFAP and Iba-1, respectively) by immunohistochemistry. Treatment with LPS induced anxiogenic and depressive-like behaviors, cognitive and motor coordination deficits, elevated levels of cytokines TNF-α and IL-1β, increased oxidative stress parameters (MDA and nitrite), decreased GSH and altered levels of specific neurotransmitters promoted an increase in areas marked by GFAP and Iba-1. In addition to causing histopathological changes such as: presence of a pcynotic nucleus, retraction of the neuronal body, vascular congestion, vacuolization and edema. Scopolamine induced cognitive deficit and changes in motor coordination, increased MDA and nitrite levels, but reduced GSH in the areas studied, decreased dopamine and GABA levels, but increased glutamate. It was able to cause histopathological changes and increase areas marked by GFAP and Iba-1. Levofloxacin at a dose of 100mg/kg did not change behavioral parameters, increased MDA levels in the prefrontal cortex and hippocampus, but did not significantly alter the expression of pro inflammatory interleukins (TNF-α and IL-1β) nor the expression of specific neurotransmitters. However, levofloxacin at a dose of 150 mg/kg was capable of inducing cognitive and motor coordination deficits, as well as depressive-like behavior; increased MDA and nitrate-nitrite levels, but reduced GSH; significantly altered the expression of TNF-α and IL-1β; increased glutamate levels and decreased GABA. Both doses studied promoted an increase in areas marked by GFAP and Iba-1, in addition to causing histopathological changes.